2005
DOI: 10.3852/mycologia.97.5.1067
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and taxonomy of the North American clade of the Ceratocystis fimbriata complex

Abstract: Ceratocystis fimbriata is a widely distributed, plant pathogenic fungus that causes wilts and cankers on many woody hosts. Earlier phylogenetic analyses of DNA sequences revealed three geographic clades within the C. fimbriata complex that are centered respectively in North America, Latin America and Asia. This study looked for cryptic species within the North American clade. The internal transcribed spacer regions (ITS) of the rDNA were sequenced, and phylogenetic analysis indicated that most isolates from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 38 publications
3
68
0
1
Order By: Relevance
“…Of the other members of the Ceratocystidaceae within the geographic distribution of C. platani in Europe and Asia Minor (Tsopelas et al 2017), Endoconiophora coerulescens and E. resinifera were detected occasionally at 5 ng or 500 pg per reaction, but these species are only known in wood of Pinaceae (Harrington & Wingfield 1997). There may be some geographic overlap for C. harringtonii or C. variospora with C. platani in the USA (Johnson et al 2005), but these and the other tested species are not known to colonize Platanus spp., and C. platani is highly specific to this host (Baker et al 2003.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 96%
“…Of the other members of the Ceratocystidaceae within the geographic distribution of C. platani in Europe and Asia Minor (Tsopelas et al 2017), Endoconiophora coerulescens and E. resinifera were detected occasionally at 5 ng or 500 pg per reaction, but these species are only known in wood of Pinaceae (Harrington & Wingfield 1997). There may be some geographic overlap for C. harringtonii or C. variospora with C. platani in the USA (Johnson et al 2005), but these and the other tested species are not known to colonize Platanus spp., and C. platani is highly specific to this host (Baker et al 2003.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 96%
“…Under the dual nomenclature system, the asexual states of Ceratocystis species were treated in the genus Chalara (Nag Raj and Kendrick 1975) and were more recently consolidated in Thielaviopsis (Paulin-Mahady et al 2002). Based on DNA sequence analyses, it is now recognized that there are distinct phylogenetic lineages in Ceratocystis, defining complexes in which species have similar morphological and ecological characteristics (Harrington et al 1996, Harrington and Wingfield 1998, Baker et al 2003, Johnson et al 2005, van Wyk et al 2006. Indeed, it has been suggested that some of these lineages represent discrete genera .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the taxonomic literature of Ceratocystis during the past decade, the endoconidia have been described consistently as of two forms. These have been referred to as cylindrical versus doliform endoconidia (Baker-Engelbrecht andHarrington 2005, Johnson et al 2005) or by other authors as primary versus secondary conidia (van Wyk et al 2006(van Wyk et al , 2007(van Wyk et al , 2009(van Wyk et al , 2011Heath et al 2009). For the purpose of the present study we define the endoconidia produced in phialides as primary conidia when they are aseptate, hyaline and cylindrical.…”
Section: Introductionmentioning
confidence: 99%
“…This fungus is a member of the Latin American clade of the Ceratocystis fimbriata complex [1,2], a taxonomic group that includes species with high genetic variability and wide host ranges [3,4]. These species cause canker and wilt diseases in many economically important crops, such as Coffea arabica and Eucalyptus spp.…”
Section: Introductionmentioning
confidence: 99%
“…C. cacaofunesta is indigenous to Central and South America [1,2]. In Brazil, this pathogen was first reported in the Amazon region [7].…”
Section: Introductionmentioning
confidence: 99%